Television and identities: analysis of the consumption of 'telenovelas' by the Latin American community in Spain. Issue 5 (2nd September 2016) - Morales, Fernando; Simelio, Núria
Abstract : This article analyses the consumption of 'telenovelas' by Latin American residents in Spain. Our hypothesis is that 'telenovelas' are a way of constructing identities especially in communities that have emigrated to other countries and which can be seen in their specific viewing preferences for fiction. We have carried out a survey following the methodology applied in these kinds of studies. The survey was applied to 219 Latin American subjects who reside in Spain. We demonstrate that the main factors influencing the consumption of 'telenovelas' by the Latin American community residing in Spain are related to the cultural identities of the countries of production and which are represented in the context of the different storylines, such as natural locations, costumes and language. The results show that further research in this field is needed in order to identify the derivations of perceptions by the immigrant collectives through successful products such as 'telenovelas'.